2015
DOI: 10.1037/a0039344
|View full text |Cite
|
Sign up to set email alerts
|

Setting the stage for an evidence-based model of psychotherapy supervisor development in clinical psychology.

Abstract: In this study, we use a "best evidence synthesis" (BES) approach to help build an evidence-based model of psychotherapy supervisor development. First, a definition of psychotherapy supervisor development was created using Milne's (2007) framework of 4 criteria necessary for a useful definition. This definition combined Watkins' (2012a) definition of psychotherapy supervisor development with elements from Falender et al. 's (2004) statement on defining competencies in clinical supervision. Second, the resultan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…The broader goal would be to examine whether, and how, ScoL-oriented supervision instruction contributes to effectiveness of supervisors and, subsequently, their counselors. Such studies might help address critiques of supervision training research as "unfocused and atheoretical" (Gosselin et al, 2015, p. 388) and lacking in rigor (e.g., Gosselin et al, 2015;Watkins, 2012). Application and examination of ScoL principles in other supervision contexts also might be fruitful, including supervision of supervision, supervision training for master's-level practitioners, as well as supervision practice itself.…”
Section: Discussionmentioning
confidence: 99%
“…The broader goal would be to examine whether, and how, ScoL-oriented supervision instruction contributes to effectiveness of supervisors and, subsequently, their counselors. Such studies might help address critiques of supervision training research as "unfocused and atheoretical" (Gosselin et al, 2015, p. 388) and lacking in rigor (e.g., Gosselin et al, 2015;Watkins, 2012). Application and examination of ScoL principles in other supervision contexts also might be fruitful, including supervision of supervision, supervision training for master's-level practitioners, as well as supervision practice itself.…”
Section: Discussionmentioning
confidence: 99%
“…Preliminary analyses indicated that the unweighted and weighted composite scores yielded comparable scales in terms of kurtosis and skew. Although both approaches yielded similar results, the weighted approach captured the differences in supervision between graduate student supervisors and professional supervisors; that is, in addition to other variables such as training, competency to supervise develops over time and with professional experience (see research syntheses by Gosselin, Barker, Kogan, Pomerleau, & d′Ioro, 2015, and Watkins, 2012). Specific supervision strategies were first weighted and then summed to create composite scores, with higher scores indicating more supervision experiences ( M = 15.18, SD = 6.78, range = 2–36 out of 48).…”
Section: Methodsmentioning
confidence: 99%
“…Using Shulman's (2005b) signature pedagogy language, most supervision research to date is focused on surface (interventions supervisors use) and implicit (values addressed in supervision, such as gatekeeping and cultural responsiveness) dimensions, with much less attention on its deep structures (e.g., pedagogical foundations). Indeed, despite a large body of supervision literature in counseling journals, research about both supervision practice and supervision training rarely are grounded in pedagogy (Bernard & Luke, 2015;Borders, 2019), not unlike supervision literature in other professions (e.g., Gosselin et al, 2015;Olds & Hawkins, 2014). Perhaps ironically, more work is needed to understand the pedagogy underlying counseling's signature pedagogy.…”
Section: New Research Questionsmentioning
confidence: 99%